Efficacy and Safety of Spinal Anaesthesia in Paediatric Age Group between 3 to 14 Years for Infraumblicus Surgery - Gautam, Shailendra Nath; Acharya, S.; Bajracharya, G.R.; Hyoju, S. (Nepal Medical College Journal, 2019)
Spinal anaesthesia (SA) in paediatric patients was first introduced by August Bier in 1899. But this technique did not gain wide spread popularity in paediatric age group because of the introduction of various muscle relaxants and inhalational agents for general anaesthesia. SA in paediatric population has been gradually reintroduced as an alternate to general anaesthesia. The study was performed at the Nepal Medical College Teaching Hospital to evaluate the efficacy and safety of SA in paediatric age groups, compare the change in vital parameters such as heart rate, blood pressure and oxygen saturation during preoperative and intraoperative period, the complications of SA and time of demand for first rescue analgesia in postoperative ward. Sixty-seven patients aged between 3 years to 14 years of ASA I and ASA II were selected after screening for anaesthesia fitness. The duration of surgery ranged from 49.85 ± 11.55 to 56.30 ± 9.68 minutes and the blood loss was less than 10% of total blood volume, thus there was no need to transfuse during operation. The duration of analgesia ranged between 107.69 ± 7.25 to 115.00 ± 7.07 minutes in different age groups. Sixty patients (89.55%) achieved Bromage Scale Score (BSS) 3 with interpretation of complete block; seven patients (10.45 %) achieved Bromage Scale Score 2 (partial block) and were operated after supplemental intravenous sedation. None of the patients needed conversion to general anaesthesia. Successful CSF drain with placement of spinal needle in 1st attempt was achieved among 55 patients (82.1%) and in 2nd attempt among 12 patients (17.9%). No unsuccessful attempt was recorded. SA in children appears to be a relatively safe technique with few complications and may be considered as an alternative for general anaesthesia. It is cost effective in comparison to general anaesthesia as the drugs and equipment required are less and cheaper and the length of hospital stay is usually shorter.